2009
DOI: 10.1111/j.1349-7006.2009.01334.x
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor receptor 3 mutation in voided urine is a useful diagnostic marker and significant indicator of tumor recurrence in non‐muscle invasive bladder cancer

Abstract: The fibroblast growth factor receptor (FGFR)-3 gene encodes a receptor tyrosine kinase that is frequently mutated in non-muscle invasive bladder cancer (NMIBC). A sensitive and quantitative assay using peptide nucleic acid-mediated real-time PCR was developed for detecting FGFR3 mutations in the urine samples and evaluated as a molecular marker for detecting intravesical recurrence of NMIBC in patients undergoing transurethral resection of bladder tumor. FGFR3 mutation was examined in tumor tissues and seriall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 23 publications
3
46
0
4
Order By: Relevance
“…We found that it was overexpressed compared to normal CD19þ cells. Unlike multiple myeloma, WM neoplastic cells lack immunoglobulin heavy chain locus translocations (4,14,19). These findings are in agreement with previous reports showing that overexpression of wildtype FGFR3 in B lymphoid cells was oncogenic and cooperated with MYC to accelerate development of Bcell lineage neoplasms (20).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We found that it was overexpressed compared to normal CD19þ cells. Unlike multiple myeloma, WM neoplastic cells lack immunoglobulin heavy chain locus translocations (4,14,19). These findings are in agreement with previous reports showing that overexpression of wildtype FGFR3 in B lymphoid cells was oncogenic and cooperated with MYC to accelerate development of Bcell lineage neoplasms (20).…”
Section: Discussionsupporting
confidence: 82%
“…The extracellular portion of FGFR3 interacts with FGF3, setting in motion a cascade of downstream signals, ultimately influencing mitogenesis and differentiation (2). FGFR3 was shown to play a major role in several types in cancer; it was shown to mediate growth and neoplasia in colorectal (3), bladder (4), and oral (5) cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 63 reports selected for detailed evaluation, 33 were excluded as duplications or because they lacked key data. The final meta-analysis was carried out on the remaining 30 studies (Billerey et al, 2001;Kimura et al, 2001;Bakkar et al, 2003;Rieger-Christ et al, 2003;van Rhijn et al, 2003van Rhijn et al, , 2004Hernández et al, 2005;Jebar et al, 2005;van der Aa et al, 2005;Wallerand et al, 2005;Hernández et al, 2006;Lindgren et al, 2006;Tomlinson et al, 2007;van Oers et al, 2007;Burger et al, 2008;Junker et al, 2008;Eltze et al, 2009;Ouerhani et al, 2009;van Oers et al, 2009;Zieger et al, 2009;Bakkar et al, 2010;Bodoor et al, 2010;Kompier et al, 2010;Miyake et al, 2010;van Rhijn et al, 2010;Al-Ahmadie et al, 2011;Dodurga et al, 2011;Serizawa et al, 2011;Sjödahl et al, 2011;van Rhijn et al, 2012). Twenty-five of the studies (Table 1A) investigated the association between FGFR3 mutations and grade or stage, while the other 13 studies (Table 1B) investigated the prognostic value of FGFR3 mutations for BC.…”
Section: Resultsmentioning
confidence: 99%
“…FGFR3 mutations have also been detected in >70% of non-muscle-invasive bladder tumors, but they have only been detected in 10-20% of tumors that invade the bladder muscle. Although a number of studies have reported that FGFR3 mutations are significantly associated with low tumor grade and early cancer stages, other studies have shown that they are not (Bodoor et al, 2010;Miyake et al, 2010). Therefore, the prognostic value of FGFR3 remains controversial (Cheng et al, 2011;Mukhtar and Perry, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…The high recurrence rate (60-80%) of noninvasive tumors requires long-term, expensive patient monitoring. Recent data suggest that detection of FGFR3 mutations in urine from patients with FGFR3 mutations in the primary tumor indicates recurrence (101,102). Thus, identification of FGFR3 mutations is not only a potential biomarker for bladder cancer diagnosis and prognosis but could also indicate tumor recurrence.…”
Section: Fgfr Mutationsmentioning
confidence: 99%